2019
DOI: 10.1187/cbe.19-04-0080
|View full text |Cite
|
Sign up to set email alerts
|

Using a Reconciliation Module Leads to Large Gains in Evolution Acceptance

Abstract: Too many students reject the theory of evolution because they view it as incompatible with their religious beliefs. Some have argued that abandoning religious belief is the only way to help religious individuals accept evolution. Conversely, our data support that highlighting faith/evolution compatibility is an effective means to increase student acceptance. We surveyed students enrolled in entry-level biology courses at four religiously affiliated institutions. At each university, teachers gave students a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 39 publications
2
35
1
1
Order By: Relevance
“…This study confirms prior research (Lindsay et al 2019 ) that a reconciliatory approach is an effective way of helping students come to accept evolution. Although the gains in evolution acceptance in the biology classroom were significantly higher than the gains in the theology classroom, this research shows that a theology classroom could be a viable setting for increasing student acceptance of evolutionary theory.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study confirms prior research (Lindsay et al 2019 ) that a reconciliatory approach is an effective way of helping students come to accept evolution. Although the gains in evolution acceptance in the biology classroom were significantly higher than the gains in the theology classroom, this research shows that a theology classroom could be a viable setting for increasing student acceptance of evolutionary theory.…”
Section: Discussionsupporting
confidence: 91%
“…In this current study, both instructors implement one of the suggested ReCCEE practices, highlighting potential compatibility, and from this point forward will be labeled as a reconciliatory approach. Lindsay et al ( 2019 ) found that a reconciliatory approach accompanied by NOS instruction led to gains in evolution acceptance among undergraduates of several different Christian denominations. Surprisingly, even when instructors know that this approach can be effective, many still take an antagonistic view toward religion when teaching evolution (Barnes and Brownell 2016 ).…”
Section: The Influence Of Religiositymentioning
confidence: 99%
See 1 more Smart Citation
“…As stated earlier, the predominant religion in Utah County is CJCLDS, with one of the Universities surveyed being affiliated with that church. Religion, and especially the religious views of Latter-Day Saints, has proven in the past to be an important factor in political stances, trust in science, and evolutionary acceptance (47,66,67).…”
Section: Differences Between Populationsmentioning
confidence: 99%
“…Instructors can reduce perceived conflicts between evolution and religion by providing specific examples that demonstrate compatibility between the two and weaken the false dichotomy between them. This practice is highly recommended in previous literature on evolution education [28,[33][34][35][36].…”
mentioning
confidence: 99%